High expression of matrix metalloproteinases: MMP-2 and MMP-9 predicts poor survival outcome in colorectal carcinoma. (February 2016) - Salem, Nada; Kamal, Ibrahim; Al-Maghrabi, Jaudah; Abuzenadah, Adel; Peer-Zada, Abdul Ali; Qari, Yousif; Al-Ahwal, Mahmoud; Al-Qahtani, Mohammed; Buhmeida, Abdelbaset
Aim: To evaluate the expression pattern of matrix metalloproteinases (MMPs); MMP-2, MMP-7 and MMP-9 in colorectal cancer (CRC) and determine its prognostic potential.Patients & methods: CRC samples of 127 patients were studied. Protein expressions of MMP-2, -7 and -9 were analyzed by immunohistochemistry and association with clinicopathological variables was statistically analyzed.Results: Overexpressions of MMP-2 and MMP-9 correlated with poor outcome as evaluated by univariate Kaplan–Meier for disease-free survival (p = 0.04, p = 0.0001) and disease-specific survival (p = 0.01, p = 0.01), respectively. Cox analysis of MMP-2 and -9 were significant independent predictors of disease-free survival (p = 0.006, p = 0.018) and disease-specific survival (p = 0.004, p = 0.049), respectively.Conclusion: MMPs expression patterns provide useful prognostic information in CRC, while predicting the patients at high risk for recurrent disease.